2013
DOI: 10.5603/cj.2013.0007
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of invasive treatment in very elderly Polish patients with non-ST-segment-elevation myocardial infarction from 2003–2009 (from the PL-ACS registry)

Abstract: Background: Elderly patients with non-ST-segment elevation myocardial infarction (NSTEMI) are rarely included in randomized trials due to concomitant diseases. As a result, invasive treatment and aggressive pharmacotherapy are used less frequently in this group. The aim of the study was to analyze the impact of invasive treatment used for elderly patients (≥ 80 years) with NSTEMI from 2003-2009 and its impact on 24-month outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Multivariable analysis confirmed the significant invasive strategy contribution to outcomes which appear to be continuously better than previously reported [4,9,15].…”
Section: Discussionsupporting
confidence: 65%
“…Multivariable analysis confirmed the significant invasive strategy contribution to outcomes which appear to be continuously better than previously reported [4,9,15].…”
Section: Discussionsupporting
confidence: 65%
“…Outcomes adjusted for confounding factors in propensity score analyses 18. The Polish Registry of Acute Coronary Syndromes (PL-ACS) enrolled patients in a nationwide, prospective study of consecutively hospitalised patients aged ≥80 years with NSTEMI in 2003–2009 19. The study reported outcomes for propensity matched subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…II). Similar factors, with the exception of hypertension, were more prevalent in the patients in our study than in individuals with STEMI [18] and in octogenarians with NSTEMI [19]. Compared with the historical control, the patients in our study with PAD with acute ischemic stroke [20] presented significantly more frequently with a smoking habit, dyslipidemia and past myocardial infarction (Tab.…”
Section: Resultsmentioning
confidence: 49%
“…The prevalence of respective atherosclerosis risk factors in comparison to the data from large epidemiological studies on Polish populations (POLSCREEN, 400 Towns Project, WOBASZ, NATPOL PLUS) [16], as well as a comparison of these risk factors to recent data concerning the frequency of atherosclerosis risk factors in patients with chronic coronary syndromes (POLSCREEN CAD) [16], acute coronary syndromes [17], both with sustained ST-segment elevation (STEMI) [18] and with non-sustained ST-segment elevation (NSTEMI) [19], in addition to acute cerebral manifestations of vascular disease (a large Polish study was not available) [20].…”
Section: Main Outcomes Measuredmentioning
confidence: 99%